Extracorporeal Cytokine Removal in Critically Ill COVID-19 Patients: A Case Series - Virág, Marcell; Rottler, Máté; Ocskay, Klementina; Leiner, Tamás; Horváth, Balázs; Blanco, Daniel Adam; Vasquez, Alexa; Bucsi, László; Sárkány, Ágnes; Molnár, Zsolt (Frontiers in Medicine, 2021)
Introduction: Extracorporeal hemoadsorption (HA) is a potential adjunctive therapy in severe cases of COVID-19 associated pneumonia. In this retrospective study we report data from critically ill patients treated with HA during the first and second wave of the pandemic. Patients and methods: All patients, who received HA therapy with CytoSorb within the first 96 hours of intensive care unit (ICU) admission without hospital-acquired bacterial superinfection, were included. Clinical and laboratory data were collected: on admission, before (TB) and after (TA) HA therapy. Results: Out of the 367 COVID-19 cases, 13 patients were treated with CytoSorb, also requiring mechanical ventilation and renal replacement therapy. All patients were alive at the end of HA, but only 3 survived hospital stay. From TB-TA there was a tendency of decreasing norepinephrine requirement: 193.7 [IQR: 34.8-270.4] to 50.2 [6.5-243.5] ųg/kg/day and increasing PaO2/FiO2 ratio 127.8 (95% CI: 96.0-159.6) to 155.0 (115.3-194.6) mmHg but they did not reach statistical significance (p = 0.14 and 0.58, respectively). Treatment related adverse events were not reported. Conclusion: The treatment was well tolerated, and there was a tendency towards an improvement in vasopressor need and oxygenation during the course of HA. These observations render the need for prospective randomized trials.